Formulation and Physical Evaluation of Peel-Off Gel Mask Preparation from Cucumber Extract (Cucumis Sativus L.) - Bioto, Yakob; Thomas, Nurain; Mo'o, Faradila Ratu Cindana; Puluhulawa, Lisa Efriani (Jurnal Literasi Mandiri, 2025)
Cucumber (Cucumis Sativus L.) is one of the fruit vegetables widely consumed in Indonesia in its fresh form and contains a liquid rich in vitamins and minerals. Cucumber liquid is beneficial for refreshing the skin and moisturizing the face, thus it needs to be developed into a peel-off gel mask. This study aims to determine the formulation and evaluation of a peel-off gel mask preparation using cucumber extract. The study began with the optimization of the viscolam gel base to assess its consistency using three different concentrations (5%, 10%, and 15%). Among these concentrations, 5% viscolam produced a gel with good consistency and clarity. Subsequently, a peel-off gel mask formulation was developed with an active ingredient concentration of 2.5% and 5% viscolam. The evaluation of the mask preparation included viscosity testing, pH testing, organoleptic testing (color, aroma, texture), homogeneity, spreadability, adhesion, drying time, and hedonic testing. The results of the study show that the formulation of the peel-off gel mask from cucumber extract has good physical properties and meets the requirements for use on the skin.